Strategi Efektif Mengubah Generalisasi Menjadi Pemahaman Konkret Untuk Siswa Sekolah Dasar - Agustina, Utari; Adila, Nur; Syarifuddin, Syarifuddin (JUPE : Jurnal Pendidikan Mandala, 2024)
This article discusses effective strategies for turning generalizations into concrete understanding among elementary school students. By using active learning methods, concrete manipulatives, and context-based approaches, this research aims to improve students' ability to understand abstract concepts. This research was conducted in several elementary schools involving 150 grade 4 and 5 students as subjects. The results showed a significant increase in understanding of math and science concepts after implementing this strategy.